2015
DOI: 10.1063/1.4920936
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on electronic and optical properties of Cu2ZnSiV I4 (VI=S, Se, and Te) quaternary semiconductors

Abstract: The electronic and optical properties of Cu2ZnSiS4, Cu2ZnSiSe4 and Cu2ZnSiTe4 in kesterite and stannite structures are systematically studied using first-principles calculations. Crystal field splitting, optical transitions, p-d bonding, and anti-bonding overlapping are analyzed. The physical and chemical trends in these properties are investigated with respect to the crystal structure and anion atomic number. The optical spectra, such as dielectric function, refractive index, reflectivity and absorption coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
4
8
0
Order By: Relevance
“…On the other hand, it can be noted from Table that the tetragonal distortion parameter η = c /2 a is smaller than unity ( η = 0.995) for the present α‐Cu 2 ZnGeTe 4 with KS structure. This is consistent with first principles electronic structure calculations for Cu2BIICIVX4VI quaternaries indicating that in general η < 1 for the KS but η > 1 for the ST structure. For example, for Cu 2 ZnGeTe 4 the calculated value of η is 0.994 for KS and 1.003 for ST structures .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, it can be noted from Table that the tetragonal distortion parameter η = c /2 a is smaller than unity ( η = 0.995) for the present α‐Cu 2 ZnGeTe 4 with KS structure. This is consistent with first principles electronic structure calculations for Cu2BIICIVX4VI quaternaries indicating that in general η < 1 for the KS but η > 1 for the ST structure. For example, for Cu 2 ZnGeTe 4 the calculated value of η is 0.994 for KS and 1.003 for ST structures .…”
Section: Resultssupporting
confidence: 89%
“…These compounds are known to crystallize either in tetragonal structures (space groups I true4¯2 m , P true4¯, or I true4¯) or in the orthorhombic wurtz–stannite superstructure (space group Pmn 2 1 ) which are derived from the sphalerite or wurtzite cells, respectively, by ordering of the metals on the cation sites. Minor attention has been devoted to the Cu 2 B II C IV Te 4 members of this family and their physical and chemical properties were only scarcely discussed in the literature . However, the phase relations and crystal structure of the compound Cu 2 ZnGeTe 4 have been studied in some detail by Parasyuk et al by using differential thermal analysis (DTA) and X‐ray powder diffraction (XRD) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…1 [6] and theoretical studies [7]. As expected, the lattice constants decrease monotonically and almost linearly for increasing Ge and Si-content because of the larger atomic covalent radius of Sn (1.45 Å) compared to those of Ge (1.25 Å) and Si (1.10 Å).…”
Section: Computational Detailsmentioning
confidence: 62%
“…Incorporation of Ge or Si in CZTSSe has been suggested as one way to increase the PCE as well as the crystalline stability of high‐quality CZTSSe . For instance, by alloying Sn with Ge atoms in CZTSe, the band‐gap energy of Cu 2 ZnSn 1− x Ge x Se 4 can be varied from 1.1 to 1.45 eV when increasing x from 0 to 1 .…”
Section: Introductionmentioning
confidence: 99%
“…alloys. Incorporation of Ge or Si in CZTSSe has been suggested as one way to increase the solar cell efficiency as well as the crystalline stability of high-quality CZTSSe [14][15][16][17][18][19][20]. It has been shown that the presence of Ge in CZTSe (i.e., Se as anions) can tune the gap energy to be close to the optimal value of ~1.3 eV [15,17,19] with an improved stability of the absorber layer in solar cells [16].…”
Section: Czts Cation Alloysmentioning
confidence: 99%